Evaluating the quality of environmental baselines for deep seabed mining - Christiansen, Sabine; Bräger, Stefan; Jaeckel, Aline (Frontiers in Marine Science, 2022)
Generating environmental baseline knowledge is a prerequisite for evaluating and predicting the effects of future deep seabed mining on the seafloor and in the water column. Without baselines, we lack the information against which to assess impacts and therefore cannot decide whether or not they pose an acceptable risk to the marine environment. At present, the International Seabed Authority (ISA), which is the international regulator for seabed mining, requires contractors engaged in mineral exploration to establish geological and environmental baselines for their respective contract areas. However, there are no criteria for evaluating what a robust baseline entails. This paper seeks to address this gap by not only analyzing the role and importance of baselines for environmental management but also suggesting criteria for evaluating the quality of baselines. Such criteria (which we present in tabular format) should include at least a minimum amount of technical information, based on best available scientific information and process, in standardized format to enable comparison between contractors and regional synthesis. These criteria should also allow baselines to be used for before-after comparisons through the choice of appropriate zones for comparison of impacts, and to prepare and test a suite of monitoring indicators and their metrics. Baseline studies should identify uncertainties, vulnerable species and habitats, and include transparent reporting as well as exchange with independent scientists and other stakeholders. The quality criteria suggested in this paper build on the ISA’s existing Mining Code and seek to support the development of a more standardized catalogue of requirements for environmental baselines. This will allow states, mining operators, the ISA, and the public to gain a better understanding of the environmental impacts of seabed mining and available mitigation measures.